Peran Manajemen Humas dalam Meningkatkan Mutu Pendidikan di SMAN 1 Manyaran - Muhammad Syafiq; Nurul Latifah Inayati (Journal on Education, 2023)
Abstract This research activity aims to determine public relations management at SMA Negeri 1 Manyaran. This research utilizes a qualitative-descriptive based approach. The method used by the author is the phenomenological method whose goal is to find out the phenomena that exist in the community. Data analysis was carried out through several stages, including the first stage of data reduction, the second stage of data presentation, and the third stage of drawing conclusions. The results of the discussion related to public relations management at SMA Negeri 1 Manyaran include the following management that is applied, namely school-based management; there are various innovations made by school principals, teachers, staff, as well as education staff; the existence of education that is oriented towards character education, achievement, increasing aspects of religiosity, developing talents and interests, providing skills training, and post-graduation job distribution for students; the existence of good communication patterns, conducting deliberations in solving problems, accommodating aspirations for school progress, obedience to government policies; appropriate management strategy and implementation in analyzing needs, exploring school potential, and combining all the different elements so that they are synergized and integrated; there is cooperation with the community, institutions/agencies, companies, and school external parties to welcome school programs; and there are efforts to increase the competence of teachers and students in SMA Negeri 1 Manyaran.